ANALISIS SEKTOR UNGGULAN DAN PENGELUARAN PEMERINTAH DI KABUPATEN OGAN KOMERING ILIR - Anna Yulianita (Department of Development Economics, Universitas Sriwijaya, 2009)
This research analyzes the government expenditure and its effect on the leading economic sector of Regency of OKI for the period 1996-2007. The intention of this research in analyzing pre-eminent economic sector which is there are in the region of Ogan Komering Ilir, and analyzes the influence of government expenditure to pre-eminent value output economic sector in this region. From the result analyze of the LQ, there are three potential sector/exceeding that is agricultural sector, building sector, and commercial sector, hotel, and restaurant. While from calculation Shazam by using the Simple Regression got the government expenditure have an effect on positive to PDRB of the agricultural sector, building sector, and commercial sector, hotel, and restaurant. Keywords: Government Expenditure, Potential Economic Sector, PDRB, Location Quotient (LQ).